The Economic Costs of Quarterly Monitoring and Recovery Management Checkups for Adults with Chronic Substance Use Disorders - Dennis, Michael L. (2011)
Recovery management checkups (RMCs) for clients with substance use disorders reduce the time from relapse to treatment re-entry, increase treatment retention, and improve long-term outcomes. The objectives of this paper are to calculate and compare the economic costs of providing outcome monitoring (OM) only with those of providing OM + RMC in order to help understand the feasibility of disseminating this model more widely. We estimate the total and incremental costs of OM and OM + RMC using data from a recently completed randomized controlled trial with adult chronic substance users (N=446). Adding RMC to OM increased total intervention costs by about 50% per person per year ($707 to $1,283) and quarter ($177 to $321). It cost an average of $834 to identify a person in relapse and $2,699 to identify, link, and retain them in treatment. The increased costs of RMC are modest relative to the substantial societal costs of chronic substance users returning to regular use, crime, and other risk behaviors.